2023
DOI: 10.3390/nu15102366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inhibiting Butyrylcholinesterase Activity Using Fractionated Coffee Extracts Digested In Vitro in Gastrointestinal Tract: Docking Simulation and Calorimetric and Studies

Abstract: Butyrylcholinesterase (BChE) is a major enzyme from the alpha-glycoprotein family that catalyzes the hydrolysis of neurotransmitter acetylcholine (ACh), lowering the concentration of ACh in the nervous system, which could cause aggravation of Alzheimer’s disease (AD). In select pathological conditions, it is beneficial to reduce the activity of this enzyme. The aim of this study was to evaluate the degree of BChE inhibition by coffee extracts fractionated into mono- and diesters of caffeic acid/caffeine, diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Fractions were isolated from coffee extracts using the CPC technique and contained some amounts of other compounds. Fractionation and digestion of preparations from the coffee extracts were described in our previous work [ 39 ]. Coffee fractions were subjected to ITC analysis ( Table 3 ) and also to molecular docking (mixture of the main compounds of the fraction) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fractions were isolated from coffee extracts using the CPC technique and contained some amounts of other compounds. Fractionation and digestion of preparations from the coffee extracts were described in our previous work [ 39 ]. Coffee fractions were subjected to ITC analysis ( Table 3 ) and also to molecular docking (mixture of the main compounds of the fraction) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…188% (light roasted) and 220–304% (dark roasted), respectively. The concentration of caffeine in the isolated fraction rich in this compound from coffee extracts was slightly reduced as a result of digestion; in the case of green and roasted coffee extracts, by 8 and 5%, respectively [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest total phenolic content was detected in the green coffee (32.30 mg g -1 ). Grzelczyk et al (2023) indicated potential pro-health effects of enzymes contained in coffee extracts on the human organism, with the greatest potential exhibited by isolates of dichlorogenic acids from green Arabica coffee (Grzelczyk et al, 2023). Each subsequent coffee roasting at increasing temperatures reduced the content of phenolic compounds as follows: from 11.8 mg g -1 in Cinnamon roast coffee and 9.26 mg g -1 in American roast to 8.25 mg g -1 in Italian roast.…”
Section: Determination Of the Content Of Bioactive Compounds And Caff...mentioning
confidence: 99%